UPAYA PENINGKATAN PENGETAHUAN IBU BALITA MELALUI PARENTING GIZI BALITA (1-5 TAHUN) DIDESA JUBANG - Nafisah Nafisah; Anggray Duvita Wahyani (ABDI MAKARTI, 2023)
Nutritional problems will affect human resources (HR). Nutritional problems can occur due to direct factors and indirect factors. The direct factors are unbalanced nutritional intake and infectious diseases. While the indirect factors are the low availability of food at the household level, inadequate maternal parenting, and inadequate health services. Toddler nutritional status is measured based on age, weight (BB) and height (TB). based on a preliminary study conducted in the village of Jubang, stated that the highest prevalence was stunting of 11.1%, Underweight of 9.3%, and Malnutrition of 7.5%. . The counseling program was carried out in conjunction with the Posyandu program using lecture, discussion and question and answer methods. most of the education levels of mothers under five are SMA/SMK (50%) and work as housewives by 55% and there is an increase in knowledge of 2.05 points after the counseling program is carried out.